Resenha - Semantic Web Technologies: trends and research in ontology-based systems - Breitman, Karin (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2011)
Semantic Web Technologies: trends and research in ontology-based systems John Davies, Rudi Studer & Paul Warren. DOI: 10.3395/reciis.v3i1.245pt link para o texto completo: http://www.revista.cict.fiocruz.br/index.php/reciis/article/view/245/260